76.6k views
3 votes
Complete the identity

Complete the identity-example-1
User Vsarunov
by
5.3k points

2 Answers

2 votes

Answer:

Explanation:

Given expression is
(\left(\csc\left(x\right)+1\right)\left(\csc\left(x\right)-1\right))/(\cot^2\left(x\right))

Now we need to simplify that to complete the identity.


(\left(\csc\left(x\right)+1\right)\left(\csc\left(x\right)-1\right))/(\cot^2\left(x\right))


=(\csc^2\left(x\right)+1\csc\left(x\right)-1\csc\left(x\right)-1^2)/(\cot^2\left(x\right))


=(\csc^2\left(x\right)+1\csc\left(x\right)-1\csc\left(x\right)-1)/(\cot^2\left(x\right))


=(\csc^2\left(x\right)-1)/(\cot^2\left(x\right))

Apply formula


\csc^2\left(\theta\right)=1+\cot^2\left(\theta\right)


=(\cot^2\left(x\right))/(\cot^2\left(x\right))


=1

Hence required identity is


(\left(\csc\left(x\right)+1\right)\left(\csc\left(x\right)-1\right))/(\cot^2\left(x\right))=1

User Gaurav Bharadwaj
by
5.5k points
4 votes

ANSWER


(( \csc x + 1)( \csc(x) - 1))/( \cot ^(2) (x) )=1

EXPLANATION

The given identity is:


(( \csc x + 1)( \csc(x) - 1))/( \cot ^(2) (x) )

Recall that:


(x + 1)(x - 1) = {x}^(2) - {y}^(2)

We apply difference of two squares to the numerator to get:


(\csc ^(2) x - 1)/( \cot ^(2) (x) )

Also recall the Pythagorean Identity.


1 + \cot^(2) (x) = \csc ^(2) (x)

This implies that,.


\cot^(2) (x) = \csc ^(2) (x) - 1

Hence our identity becomes:


(\cot ^(2) x )/( \cot ^(2) (x) ) = 1

User Shaun Dychko
by
4.9k points